Tomaru Verb Polysemy in Japanese - Elizabeth Ika Hesti Aprilia Nindia Rini; Alif Prasetyaningtyas (Universitas Diponegoro, 2021)
Polysemy is the capacity for a word or phrase to have multiple related meanings. Tomaru verb is one of the polysemous verbs. This study aims to describe the basic meaning and the extended meaning of the verb tomaru in Japanese. Data collection in this study used the method of observing with the note-taking technique. In addition, the data analysis in this study used descriptive and agih methods. As for the presentation of the results of the analysis in this study using informal methods. Based on the results of the analysis, it can be concluded that the verb tomaru has one basic meaning and seven extended meanings. The verb tomaru basic meaning is to stop. Meanwhile, the extended meaning namely something that comes out does not come out; something that flows becomes nonflowing; something sustainable becomes unsustainable; something that comes does not come; resting temporarily in a certain place; undetached, fixed in place; and what has been seen and heard leaves an impression